Importance of directed acyclic graphs in medical education - AlleaBelle Bradshaw; Jace C. Bradshaw (Discover Education)
Abstract Medical students are taught the importance of variable relationships in scientific research. We propose augmenting this education with teaching about direct acyclic graphs (DAGs)—a graphical model used to analyze complex systems of variables. DAGs are increasingly used in medical research and education about their creation and use would be valuable.